ANALISIS STRATEGI PEMASARAN PRODUK LAPAROSCOPY DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Mudayana, Ahmad Ahid (Universitas Ahmad Dahlan, 2010)
Background : Complexity of hospital marketing strategy that have social function needed research to analyses marketing strategy have been applied by PKU Muhammadiyah Yogyakarta hospital, especially to promote Laparoscopy Product. Marketing strategy of the segmentation, targeting and positioning. The aim of the research to analyses marketing strategy of PKU Muhammadiyah Yogyakarta to promote Laparoscopy product. Method : This was descriptive research using qualitative method. The subject was director of public and financing, the chief of marketing, and patient of Laparsocopy user. Data from the resources person was analyses carefully. Result : Strategy analyses used marketing analyses, product analyses, and competitor analyses. Laparoscopy marketing segmentation was the middle and lower social class of the patient. No distinct market targeting yet of the marketing segmentation have been applying, its caused marketing not effective yet. The position of Laparoscopy product based on seven based variable those were: attribute positioning, benefit positioning, application positioning, user positioning, competitor positioning, product category positioning, and quality/price positioning. Conclusion : Laparoscopy marketing in PKU Muhammadiyah Yogyakarta have been effective insight amount of the patient who have been using of the Laparoscopy product. However, improving better services that Laparoscopy product capable become positioning product. The Laparoscopy product hoped capable to compete with the other competitor. Keywords : Strategy analyses, segmentation, marketing target, positoning product.